2016
DOI: 10.1016/j.forsciint.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Further investigations into the single metal deposition (SMD II) technique for the detection of latent fingermarks

Abstract: Single metal deposition (SMD II), a recently proposed method for the development of latent fingermarks, was investigated by systematically altering aspects of the procedure to assess their effect on the level of development and contrast achieved. Gold nanoparticle size, temperature of the deposition solution bath, and orbital shaking during detection were shown to affect the levels of development and contrast obtained. Gold nanoparticles of diameter 15-21nm were found to be most effective for satisfactory visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…The difference shown here is quite obvious, with 10% more marks going undetected on the plastic sleeves, which would justify further research into non-porous substrate interactionsparticularly plasticswith fingermark detection techniques. Previously, there has been a correlation observed in other studies between paper type and fingermark quality [10,28,29].…”
Section: Effect Of Substratementioning
confidence: 75%
“…The difference shown here is quite obvious, with 10% more marks going undetected on the plastic sleeves, which would justify further research into non-porous substrate interactionsparticularly plasticswith fingermark detection techniques. Previously, there has been a correlation observed in other studies between paper type and fingermark quality [10,28,29].…”
Section: Effect Of Substratementioning
confidence: 75%
“…SMD can develop more samples in one solution bath, without any major detriment on the quality of the fingermarks while also enhancing 50% more fingermarks than MMD. Newland et al reported producing grade 2 fingermarks (Fig. ) when using SMD on aluminum foil (among others), adding also that the method does not seem to be hindered by the environmental conditions (i.e., heat).…”
Section: Physicochemical Methodsmentioning
confidence: 99%
“…Fingermark on aluminum foil developed with single‐metal deposition . [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Physicochemical Methodsmentioning
confidence: 99%
“…Targeted development of fingerprint ridges, luminescent fingerprints and chemical probing are amongst the enhancements that can be achieved using nanoparticles (Zhao et al 2018;Li et al 2018). The nanoparticles exploited in fingerprint research include gold, silver, titanium dioxide, zinc oxide and silica nanoparticles (SNPs) (Becue et al 2007;Sodhi and Kaur 2017;Bergeron 2003;Becue et al 2008;Kim et al 2016;Newland et al 2016;Choi et al 2007;Choi et al 2008;Singh et al 2013).…”
Section: Introductionmentioning
confidence: 99%